Incidental Visualization of Hypertrophic Vasa Nervorum in a Patient With Peripheral Vascular Disease. Issue 2 (June 2022) - Bais, Kimmy S.; Franco, Michael J.; Robards, Christopher B.; Erben, Young M.; Porter, Steven B.
Vasa nervorum are the blood vessels which supply adequate oxygen to peripheral nerves. Various vascular pathologies produce inflammatory changes compromising the blood flow through the vasa nervorum. We describe a patient with peripheral vascular disease admitted for below knee amputation who was found to have hypertrophied vasa nervorum in the ipsilateral femoral and popliteal sciatic nerves.